2014
DOI: 10.1074/jbc.m113.519421
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Chaperone Hsp70 Activates Protein Phosphatase 5 (PP5) by Binding the Tetratricopeptide Repeat (TPR) Domain

Abstract: Background: Heat shock proteins bind TPR-containing proteins to facilitate client folding. Results: The TPR domain of PP5 and the C-terminal IEEVD of Hsp70 are important for binding. Conclusion: Hsp70 binds through the TPR domain and activates PP5 phosphatase activity. Significance: Small molecules to inhibit Hsp70-PP5 interaction may be an alternative approach for cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 41 publications
(51 reference statements)
0
23
0
Order By: Relevance
“…The interactions of MtSerB2 with these HSPs can have broad implications as the chaperone activities of HSP90 and HSP70 are steered by interactions with co-chaperones and this The M. tuberculosis HAD phosphatase (Rv3042c) interacts with host proteins and is inhibited… directs their activity toward specific clients. HSPs 90 and 70 are known to bind and increase the activity of phosphatases that in turn carry out multi-site dephosphorylation of HSP bound clients [40,41]. In this study we have shown that MtSerB2 mediates the dephosphorylation of various host proteins.…”
Section: Discussionmentioning
confidence: 73%
“…The interactions of MtSerB2 with these HSPs can have broad implications as the chaperone activities of HSP90 and HSP70 are steered by interactions with co-chaperones and this The M. tuberculosis HAD phosphatase (Rv3042c) interacts with host proteins and is inhibited… directs their activity toward specific clients. HSPs 90 and 70 are known to bind and increase the activity of phosphatases that in turn carry out multi-site dephosphorylation of HSP bound clients [40,41]. In this study we have shown that MtSerB2 mediates the dephosphorylation of various host proteins.…”
Section: Discussionmentioning
confidence: 73%
“…Structural analysis has revealed that PP5 contains a C-terminal catalytic domain and three N-terminal tetratricopeptide repeats (TPRs) that are unique in the phosphoprotein phosphatase family (10). PP5 is auto-inhibited by intramolecular interactions with its TPR domain (11).…”
Section: Introductionmentioning
confidence: 99%
“…2b). These proteins, including protein phosphatase 5 (PP5), Hsc70-organizing protein (HOP), and the C-terminal Hsc70-interacting protein (CHIP), bind to the C-terminal EEVD motif that is located at the end of Hsp70's lid [59][60][61][62]. Rather than impacting ATP cycling, the TPR co-chaperones appear to coordinate "hand-off" of Hsp70's clients to other pathways.…”
mentioning
confidence: 96%